Peran Audit Internal Dalam Meningkatkan Efektivitas Sistem Pengendalian Internal Persediaan (CV. SUMBER BERKAH) - Fatika Rahma Fina; Ivananur Alvira Wahono; Irda Ayu Agustin (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This research is motivated by the objective to investigate the role of internal audit in enhancing the effectiveness of the internal control system for inventory. Efficient and effective inventory management is crucial in the healthcare environment to ensure the availability of medical supplies, proper resource utilization, and cost control. The study employs a qualitative approach, collecting data through interviews with internal auditors, inventory managers, and relevant staff. Data analysis focuses on evaluating the existing internal control system, the internal audit strategies applied, and their impact on management effectiveness.